Factors Hindering The Implementation Of Law No. 18 Of 2008 On Waste Management In Penukal Abab Lematang Ilir Regency - Rosa, Mila; Erniwati, Erniwati; Agustina, Sakinah (Fakultas Hukum Dehasen, 2025)
This study aims to analyze the implementation of waste management policies in PALI Regency, referring to Law No. 18 of 2008 and Regional Regulation of PALI Regency No. 4 of 2024. Although the regulations have been normatively established to promote the 3R principles (Reduce, Reuse, Recycle) and community involvement, the findings reveal a significant gap between policy and field implementation. This research employs a descriptive qualitative method with a case study approach, utilizing in-depth interviews, observations, and document analysis. The results indicate that policy implementation remains suboptimal due to weak communication, limited resources, lack of inter-agency coordination, and low public awareness. Moreover, community initiatives such as the PALI Waste Bank have not yet received adequate support from the local government. Social and cultural barriers, including the perception that waste management is solely the government's responsibility, further hinder progress. On the other hand, there are strategic opportunities in circular economy potential and grassroots initiatives, which could be strengthened through institutional support, incentives, and digitalization of the waste management system. This study recommends strengthening local institutions, establishing formal partnerships between communities and the government, enhancing environmental education, and promoting technological innovation as crucial steps toward a sustainable waste management system in PALI Regency.